231k views
5 votes
Express the function y=5(x−6)² as a composition y=f(g(x)) of two simpler functions y=f(u) and u=g(x).

1 Answer

2 votes

Answer:

y = 5u², u=x-6

Explanation:

Given the function:


y=5(x-6)^2

We want to express f(x) as a composition of two functions.

Let u = x-6


\implies y=5u^2

Therefore, the function y=5(x−6)² as a composition y=f(g(x)) of two simpler functions y=f(u) and u=g(x)


\begin{gathered} y=5u^2\text{ where:} \\ f(u)=5u^2 \\ u=g(x)=x-6 \end{gathered}

User Vman
by
4.6k points